1994
DOI: 10.1007/bf01839268
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the attenuated anticoccidial vaccine ‘Paracox’ in broiler chickens isolated from extraneous coccidial infection

Abstract: A trial was carried out in 1-day-old broiler chicks raised for 54 days in floorpens under simulated commercial conditions, but isolated from all extraneous virulent coccidial infections, to demonstrate the safety of 'Paracox' attenuated vaccine administered at the recommended dose when chicks were 7 days old. The vaccine did not adversely affect the water consumption, faecal moisture or litter condition of the broilers. Recycling of the attenuated coccidia occurred in vaccinated birds, oocysts being present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 6 publications
0
21
1
3
Order By: Relevance
“…The higher proportion (24%) of sampled birds found to have lesions, compared with the 4% reported by Williams (1994), is probably accounted for by the fact that sampling was carried out daily in the present experiment, but only on three separate weekly occasions in the previous study. The combined results of the two experiments show that secondary lesions may occur in broilers up to at least 40 days after vaccination with Paracox vaccine.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The higher proportion (24%) of sampled birds found to have lesions, compared with the 4% reported by Williams (1994), is probably accounted for by the fact that sampling was carried out daily in the present experiment, but only on three separate weekly occasions in the previous study. The combined results of the two experiments show that secondary lesions may occur in broilers up to at least 40 days after vaccination with Paracox vaccine.…”
Section: Discussioncontrasting
confidence: 59%
“…However, lesions have been seen in commercial chickens vaccinated with Paracox (Schering-Plough Animal Health, Harefield, UK) (for example, Bushell et al, 1990;Bushell, 1992;Shirley et al, 1995), but in all but one case it was unclear at the time whether they were due to the attenuated vaccine per se or to a wild-type challenge. The first clue was the identification of mild lesions, in 4% of 150 broilers vaccinated with Paracox, between 26 and 40 days after vaccination in a floor pen trial in a facility protected from extraneous coccidial infections (Williams, 1994). A confirmatory experiment to establish whether vaccination with attenuated coccidia can give rise to lesions without any additional challenge from extraneous parasites is the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Wet litter may result from subclinical necrotic enteritis, not seen in these trials but often observed in broilers in northern Europe, even when antibiotic growth promoters and ionophore anticoccidial drugs are used (Williams et al, 1999). The final litter moisture contents observed in these Italian trials (18.5 to 21.0% after 36/37 days; 20.6 to 22.9% after 56 days) (Table 3) were generally a little lower than the means of 25.8% (Williams, 1994) and 24.3% (Williams et al, 1999) obtained in trials in the cooler temperate climate of the UK.…”
Section: Discussionmentioning
confidence: 79%
“…An advantage of attenuated vaccines is that they have low reproductive potentials, thus avoiding crowding in the specific mucosal areas of infection and resulting in the development of optimal immunity with minimal tissue damage (105). It is believed that the drug-sensitive, attenuated strains and wild, native strains interbreed, reducing both virulence and drug resistance in local populations.…”
Section: Vaccinationmentioning
confidence: 99%